2009
DOI: 10.3390/molecules14082909
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Cyperus rotundus L. from South Africa

Abstract: The essential oils from the rhizomes of Cyperus rotundus L. collected from two different locations (Empangeni-A and KwaDlangezwa-B; both in the Kwa-Zulu Natal Province of South Africa) were obtained by hydrodistillation and analyzed by capillary GC and GC/MS. Forty-one and 43 components were identified, representing 89.9% and 92.0% of sample A and sample B, respectively. α-Cyperone (11.0%), myrtenol (7.9%), caryophyllene oxide (5.4%) and β-pinene (5.3%) were major compounds in the oil of sample A. The main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 40 publications
1
49
0
8
Order By: Relevance
“…About seventy volatiles were analyzed by SPME-headspace and GC/GC-MS of essential oil as follows: valencene (5.1%), trans-pinocarveol (7.4%), caryophyllene oxide (7.8%), valerenal (8.7%), cyperene (11.7%) and α-copaene (12.1%). Essential oil studies of aerial parts or roots of C. rotundus obtained by hydrodistillation show the dominance of the sesquiterpenoids [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About seventy volatiles were analyzed by SPME-headspace and GC/GC-MS of essential oil as follows: valencene (5.1%), trans-pinocarveol (7.4%), caryophyllene oxide (7.8%), valerenal (8.7%), cyperene (11.7%) and α-copaene (12.1%). Essential oil studies of aerial parts or roots of C. rotundus obtained by hydrodistillation show the dominance of the sesquiterpenoids [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The major components were cyperene (37.9%) and cyperotundone (11.2%). Lawal and Oyedeji [23] studied from essential oils from rhizomes of C. rotundus collected from two locations Kwa-Zulu Natal Province of South Africa. After the hydrodistillation of rhizomes essential oils analyzed by GC and GC-MS technique.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic molecules can pass through the cell wall of Gram-positive bacteria easier than the Gram-negative bacteria because the cell wall of the Grampositive bacteria contained only peptidoglycan [9]. Also some studies showed that amongst the Gram-positive and Gram-negative bacteria, Gram-positive bacteria S. aureus were inhibited by plant extract [2,7]. Based on our experimental results, the extracts obtained from Cyperus species (C. longus and C. difformis) showed considerable antibacterial properties against typical food-borne pathogens especially Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Previous phytochemical studies on this plant have revealed the presence of alkaloids, flavonoids, glycosides, furochromones, and many new sesquiterpenes.…”
Section: )mentioning
confidence: 99%